PERANAN PENTING UMKM UNTUK MENOPANG STABILITAS KEUANGAN DAN PEREKONOMIAN NASIONAL - Hendi Kurnia Mubarok; Maulana Rifai; Rahman Rahman (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Given that small and medium-sized businesses are extremely involved in workforcedevelopment and enhancing people's well-being, MSMEs play an important role asa potential sector and contribute to the general stability of the economy. Theabbreviation for Usaha Micro, Small, and Medium is UMKM. MSMEs, on the otherhand, have a much broader meaning when viewed through a different lens anddefined in a different way. MSMEs are businesses or businesses run by individuals,households, or small business entities for business actors. Prof. Ina Primiana, asenior economist, says that UMKM is a small business that drives the developmentmovement and Indonesia's economy. In contrast, M. Kwartono Adi provided a morein-depth explanation of the definition of MSMEs, which he defined as a companywith an annual profit of no more than 200 million dollars. If a company orbusinesses meet the requirements for a microbusiness, they can be referred to asUMKM. In accordance with Regulation No. 20 of 2008, micro, small, and mediumsized enterprises (MSMEs) are distinguished according to each type of business.